ANALISIS KEPUASAN MASYARAKAT TERHADAP KUALITAS PELAYANAN DALAM PENDAFTARAN TANAH PERTAMA KALI PADA KANTOR PERTANAHAN KABUPATEN BOGOR - Hermawan, Wawan; Hakim, Dedi Budiman; Hutagaol, Manuntun Parulian (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2016)
This study aimed to analyze the level of community satisfaction to the services of land registration in Land Office of Bogor. This study is expected to find indicators as a priority in the improvement of service quality. Level of community satisfaction was measured using five dimensions, i.e. reliability, responsiveness, assurance, empathy and tangible. Based on the results of the study, the overall dimensions of service quality in the first land registration through a process of the recognition of the rights granted by Land Office of Bogor District did not meet community satisfaction. Community dissatisfaction to the quality indicator of officer was marked by the difference between the average performance score of 3,58 with an average expectation score of 3,76 in order to obtain an average score of negative gap of -0,18. Indicators which are prioritized to improve community satisfaction with quality service of land registration are the clarity of service conditions, certainty of service cost, and timeliness of certificate completion. Managerial implication of recommended increasing satisfaction of service were a need to adjust the standard conditions of service, evaluating and reviewing existing policies and policies which are no longer relevant to the current conditions, creating a standard of service that is simpler, add service information in writing, improve the knowledge and abilities of employees through education and training.